Математична теорія керування: нелінійна динаміка та інженерні застосування (за матеріалами наукової доповіді на засіданні Президії НАН України 6 листопада 2019 року) - Зуєв, О.Л. (Вісник НАН України, 2020)
У доповіді представлено новий підхід до розв'язання задачі стабілізації, що дозволяє ефективно визначати стратегії керування для широкого класу суттєво нелінійних керованих динамічних систем, зокрема математичних моделей робототехнічних комплексів та керованих інженерних конструкцій з пружними балками, пластинами та оболонками. Отримані результати застосовано до задач стабілізації та навігації мобільних роботів у середовищах з перешкодами, комп'ютерного моделювання коливань керованої оболонки в експериментах з перспективними надлегкими будівельними конструкціями, а також використано у дослідженнях проблем економії енергоресурсів і сировини у хімічній індустрії та збільшення обсягів виробництва зі збереженням витрат на вхідні ресурси. One of the most important tasks in mathematical control theory is to stabilize unstable dynamic processes by applying a feedback law. The report introduces a new approach for solving the stabilization problem, which makes it possible to effectively define control strategies for a wide class of essentially nonlinear controlled dynamical systems. The class of systems under investigation includes, in particular, mathematical models in robotics and controlled engineering structures with elastic beams, plates, and shells. The obtained theoretical results are applied to problems of stabilization and navigation of mobile robots in environments with obstacles. Computer simulation results are also presented to illustrate the vibrations of a controlled shell, which is used for experiments with novel lightweight elastic structures in civil engineering. A part of this report is devoted to the application of methods of mathematical control theory to the optimization of processes in chemical engineering in the sense of minimizing the consumption of input reactants (raw materials) or maximizing the productivity. For this purpose, a class of isoperimetric optimal control problems for nonstationary mass and energy balance equations has been solved in order to improve the performance of chemical reactors in comparison to their steady-state operation.